Effect of dietary selenium yeast supplementation on porcine circovirus type 2 (PCV2) infections in mice. - Gang Liu; Guan Yang; Guiping Guan; Yuzhe Zhang; Wenkai Ren; Jie Yin; Yordan Martínez Aguilar; Wei Luo; Jun Fang; Xinglong Yu; Tiejun Li; Yulong Yin (PLoS ONE, 2015)
The present study was performed to determine the protective role of dietary selenium (Se) yeast supplementation in porcine circovirus type 2 (PCV2) infected mice. Forty-eight Kun Ming female mice were randomly assigned to Se yeast group (0.3%Se +basal diet, n = 24) and control group (basal diet, n = 24). After 3 days of adaptive feeding and 15 days treatment with the experimental feed, mice were challenged by intraperitioneal injection of PCV2 at the dosage of 2000 TCID50 (50% tissue culture infection dose, TCID50). Serum total superoxide dismutase (SOD) activity, malondialdehyde (MDA) level, tumor necrosis factor alpha (TNF-α), C-reactive protein (CRP) and interleukin-1 beta (IL-1β) levels were measured at 5, 10, 15, 20 days post infection (dpi). The PCV2 virus load in the liver, spleen and lung, and the microscopic lesions in the liver, spleen and lung also were determined on 5, 10, 15, and 20 dpi. Dietary Se yeast supplementation decreased (Pμ0.05) the serum levels of TNF-α, but had no significant effect on the activity of SOD and the levels of MDA, CRP and IL-1β between experimental and control groups. Dietary Se yeast supplementation had little effect on the PCV2 virus load in the liver, spleen and lung. However, mice in the selenium yeast group showed a significant decrease in microscopic lesion scores in the lung and spleen compared with those in the control group (Pμ0.05). These data indicate Se yeast attenuated the PCV2 infection through altering the systemic inflammation and maintaining the normal organ morphology.